Precipitation Behavior of AlN Inclusions in Fe-0.5Al-2.0Mn Alloy Under Continuous Unidirectional Solidification Process - NguyenVan, Nghiem; Kato, Kengo; Ono, Hideki (Frontiers in Materials, 2021)
Medium Manganese Transformation Induced Plastic (Mn-TRIP) steels are expected to a new generation of advanced high strength sheet steels due to their excellent balance between material cost and mechanical properties. During the solidification process, AlN precipitates at the grain boundary, which leads to the serious deterioration of hot ductility. However, the precipitation of AlN in Mn-TRIP steel has not been clear. In this study, the chemical compositions, morphology, size distribution, and the precipitation behavior of AlN inclusion in an Fe-0.5Al-2.0Mn alloy were studied under the continuous unidirectional solidification process. The results show that there are two types of nitride inclusions in the Fe-0.5Al-2.0Mn alloy: AlN inclusion and complex inclusion of Al2O3-AlN. The planar sections of most AlN particles are hexagonal. Based on the thermodynamic calculation, it was found that the content of Al has a large effect on the stability of Al2O3 and AlN. When the content of Al increases, AlN becomes more stable than Al2O3 in the liquid iron significantly. During the solidification process, Al2O3 inclusions precipitated at the beginning of the solidification process. The precipitation of AlN inclusions occurred when the contents of Al and N exceeded the equilibrium value and grew until the end of the solidification. The precipitation conditions of AlN inclusion in the Fe-0.5Al-2.0Mn alloy during the solidification process were discussed. The precipitation and the amount of precipitate of AlN inclusions depend on the initial contents of Al, N, and O. It was found that the precipitation of AlN inclusions can be controlled by reducing the initial content of N to less than 0.0072 mass%.